EQUATIONS SOLUTION HIGH ORDERLY DOG FOOD M E TODS . CHEBYSHEV'S METHOD. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This in the article Chebyshev method high orderly iterative methods explained.Given function roots in calculation Taylor formula using reverse function iterative solutions find process learns . In the article of the method main principles , Taylor formula and high orderly iterative of processes work principle in detail illuminated .